The Essence and Specific Characteristics of the Fiscal Mechanism for Regulating the Investment Development of the National Economy - Rudenko, Viktoriia; Voloshchuk, Ruslan (European Journal of Sustainable Development, 2020)
The issues of the place and role of the state in the investment process has not lost relevance for many decades. Some scholars, appealing to the experience of developed countries, propose to minimize the role of the state in the investment sphere. This view is based on the fact that state participation cannot ensure a more efficient allocation of investment resources than a market mechanism of self-regulation. Other scholars believe that all the troubles in the economy are due to the fact that the state has minimized its influence on the investment sector, thereby causing a decrease in its activity. Obviously, both positions of scientists cannot be rejected mechanically. However, the practice of conducting investment activities in Ukraine has clearly shown that the state's departure from the investment sphere has actually cleared the way for anarchy and inconsistency in the investment process. At present, the state is obliged to influence investment activity by choosing effective means of its regulation, relying primarily on the fiscal mechanism. The article is devoted to the study of the essence of the fiscal mechanism for regulating the investment development of the national economy and the identification of its specific features. The specifics of the scientific tasks that are the subject of the study required the use of a set of special methods, the use of which helped to analyze the essence of the fiscal mechanism for regulating the investment development of the national economy and to highlight its specific characteristics. The etymology of the concept of “fisc” is considered in the article. Approaches to the interpretation of the term “mechanism” are highlighted. The economic meaning of the definition of “regulation” is substantiated. The essence of the fiscal mechanism for regulating the investment development of the national economy is determined. The specific features of the fiscal mechanism for regulating the investment development of the national economy are singled out and characterized. The study found that the impact of the fiscal mechanism on the investment development of the national economy is due to its specific characteristics and the focus of its components at solving specific problems and achieving a real effect due to financial resources that are formed, distributed and used to meet the investment needs of economic entities. Keywords: fisc, mechanism, regulation, investment development, fiscal mechanism for regulating the investment development of the national economy